مبادئ الضمان الإجتماعي في ظل الواقع الديموغرافي في الجزائر - ريمي عرفات; زيدان محمد (جامعة الوادي University Of Eloued, 2024)
تهدف هذه الورقة البحثية إلى تحليل الواقع الديمغرافي وتأثيره على أهم مبادئ الضمان الاجتماعي في الجزائر، مبرزين تطور الفئات العمرية للسكان، والتي نتج عنها زيادة في العمال الأكبر سنا وكذلك زيادة في أعداد كبار السن وبالتالي دخول الجزائر إلى أبواب مرحلة التشيخ السكاني الذي كان له أثر إيجابي وسلبي على مبادئ نظام الضمان الاجتماعي، الأثر الإيجابي متمثل في تحقيق مبدأ التغطية الشاملة لنظام الضمان الإجتماعي في الجزائر أي تمتع أغلبية السكان بالتأمين الإجتماعي، أما الأثر السلبي متمثل في زيادة عدد المتقاعدين الذي زاد من الإنفاق الإجتماعي مما أثر سلبا على موازنة الصندوق الوطني التقاعد في الجزائر. وأضفت توصيات الورقة البحثية بإثراء كفية إستغلال مبدأ التغطية الشاملة الذي يتمتع به نظام الضمان الإجتماعي في الجزائر لحل مشكل العجز في موازنة صندوق التقاعد في السنوات الأخيرة من العقد الماضي. : This research paper aims to analyze the demographic reality and its impact on the most important principles of social security in Algeria, highlighting the development of the age groups of the population, which resulted in an increase in older workers as well as an increase in the number of the elderly, and thus Algeria entered the gates of population aging, which had a positive impact And negative on the principles of the social security system, the positive impact is represented in the achievement of the principle of comprehensive coverage of the social security system in Algeria, That is, the majority of the population enjoys social insurance, and the negative impact is represented by the increase in the number of retirees, which increased social spending, which negatively affected the budget of the National Retirement Fund in Algeria And I added the recommendations of the research paper to enrich how to exploit the principle of comprehensive coverage enjoyed by the social security system in Algeria to solve the problem of deficit in the budget of the pension fund in the last years of the past decade
Principles of social security in light of the demographic reality in Algeria
Keywords: الواقع الديموغرافي; التشيخ السكاني; التأمين الإجتماعي; التقاعد; الجزائر; demographic reality; population aging; social insurance; retirement; Algeria